Appraisal of 5‐year recurrence‐free survival after surgery in pancreatic ductal adenocarcinoma. (23rd September 2020) - Yoon, So Jeong; Shin, Sang Hyun; Yoon, So Kyung; Jung, Ji Hye; You, Yunghun; Han, In Woong; Choi, Dong Wook; Heo, Jin Seok
Abstract: Background/Purpose: Pancreatic ductal adenocarcinoma (PDAC) is regarded as incurable, with a limited survival rate after curative resection. The aim of this study was to explore long‐term survival and late recurrence of PDAC after surgery. Methods: Medical data of 859 patients who underwent resection between 1995 and 2014 were retrospectively examined. The clinicopathological features of the 5‐year recurrence‐free survivors and the patients with recurrent disease after 5 years were investigated separately. Results: Among the 768 patients who were finally included in this study, elevated CA 19‐9, tumor size, poor differentiation, and positive lymph node metastasis were associated with recurrence. In 89 patients with 5‐year RFS, age, tumor size, differentiation, and lymph node metastasis were statistically significant predictive factors. Among these patients, disease relapse occurred in 11 patients; age was the only difference compared to those who remained free of recurrence. Conclusions: Most prognosticators failed to predict the risk of recurrence in the 5 years following surgery for PDAC, and recurrence can occur even at time points up to 100 months. Therefore, cure of PDAC cannot be guaranteed by a 5‐year recurrence‐free interval, and further studies into the inherent nature of PDAC are needed to develop adequate surveillance systems which may lead to improvements in survival. Abstract : In this single‐center retrospective study, Yoon and colleagues analyzed the long‐term follow‐up data of 768 patients with resected pancreatic ductal adenocarcinoma to identify the characteristics of 5‐year recurrence‐free survival and late recurrence. The results suggested the need for developing more effective surveillance systems after surgical resection of pancreatic ductal adenocarcinoma.